Special Education Of Advocates Profession As The Advocate's Professionality As A Law Enforcer - citranu ranu (Satya Sastraharing : Jurnal Manajemen, 2019)
Abstract Harmonization between The Law of Advocate and The Law of Higher Education related to Special Education of Advocates Profession is very important, the Constitutional Court has given a decision that Special Education of Advocates Profession must cooperate with accredited Higher Education This was done to achieve the objectives of the Constitution through the Law Advocates which gave birth to law enforcement with expertise, competence, and professionals in their fields. Advocates as law enforcers who uphold the Pancasila and The 1945 Constitution of The Republic of Indonesia must take constitutional education to achieve the objectives can be realized through the Law of Higher Education related to Special Education of Advocates Profession which adjusts National Education Standards and Professional Education Standards in order to maintain the quality of the profession. Keywords: Education, Advocates, Profession